Monitoring Bar Velocity to Quantify Fatigue in Resistance Training - Moura, Raony Espíndola; Bezerra da Silva, Rodrigo Fabio; Gomes, Lucas Morais de Souza; Ramos da Silva, José Leonardo; Henrique, Rafael dos Santos; Sousa, Filipe Antônio de Barros; Fonseca, Fabiano de Souza (International Journal of Sports Medicine, 2024)
We analyzed the effects of load magnitude and bar velocity variables on sensitivity to fatigue. Seventeen resistance-trained men (age=25.7±4.9 years; height=177.0±7.2 cm; body mass=77.7±12.3 kg; back-squat 1RM=145.0±33.9 kg; 1RM/body mass=1.86) participated in the study. Pre- and post-exercise changes in the mean propulsive velocity (MPV) and peak velocity (PV) in the back-squat at different intensities were compared with variations in the countermovement jump (CMJ). CMJ height decreased significantly from pre- to post-exercise (∆%=−7.5 to −10.4; p<0.01; ES=0.37 to 0.60). Bar velocity (MPV and PV) decreased across all loads (∆%=−4.0 to −12.5; p<0.01; ES=0.32 to 0.66). The decrease in performance was similar between the CMJ, MPV (40% and 80% 1RM; p=1.00), and PV (80% 1RM; p=1.00). The magnitude of reduction in CMJ performance was greater than MPV (60% 1RM; p=0.05) and PV (40% and 60% 1RM; p<0.01) at the post-exercise moment. Low systematic bias and acceptable levels of agreement were only found between CMJ and MPV at 40% and 80% 1RM (bias=0.35 to 1.59; ICC=0.51 to 0.71; CV=5.1% to 8.5%). These findings suggest that the back-squat at 40% or 80% 1RM using MPV provides optimal sensitivity to monitor fatigue through changes in bar velocity.
Keywords: velocity-based training; strength training; neuromuscular fatigue; back-squat